Transesterification of Jatropha curcas Seed Oil: Reaction Parameters - . Abdelrahman2, Maha; A. Yassin1, Atif A.; Hassan, Ismail; B. Karama, Abdallah; E.S. Mirghani 3, Mohamed (Gezira Journal of Engineering and Applied Sciences; Vol 14 No 1 (2019), 2019)
This study was carried out to determine the reaction parameters of the fatty acid methyl ester (FAME) and yield produced from Jatropha curcas ( J. curcas ) oil by alkali transesterification. Optimum reaction parameters were observed at 1:6 w/w methanol to oil ratio, 0.5% w/w NaOH to oil molar ratio, 400 rpm agitation speed and 60 ⁰C with resulted in a yield of 99% crude biodiesel and 97.71% FAME.